2nd PERPUN International Conference and Workshop on Value Management for Libraries : Towards Excellence Through ROI, 27-28 September 2012 - Centre for Academic, Information Services (2012)
Fail ini mengandungi dokumen seperti 1. A workbook for a one-day workshop: Towards Excellence Through ROI - Morning Session, Presented by Joseph Matthews -- 2. A workbook for a one-day workshop: Towards Excellence Through ROI - Afternoon Session, Presented by Joseph Matthews -- 3. Turpion Journal Archive : The finest collection of articles from Russian Scientists 1958-2001 -- 4. Unlock contents with seamless navigation -- 5. RDA Moving Forward! -- 6.Summon -- 7. Online literature and drama collections -- 8. Proquest dissertations and theses